Histoire, Mémoire et Identités dans l’Argentine du Bicentenaire (2010) - Natalia Molinaro (Conserveries Mémorielles)
This article develops certain themes broached in my doctoral thesis. The subject of discussion is the official bicentenary commemoration of the May 1810 Revolution, organised by the Argentinian government in Buenos Aires during the week of 18 and 25 May 2010. After explaining the methodological approach to studying the event, the article goes on to explore certain socio-political issues around the commemoration and the general context of post-crisis Argentina. Some of the fundamental aspects of the ceremonial rite employed on the evening of 25 May 2010 are considered here : for example, the reconstruction of the manner in which national identity is represented and the reinvention of Argentinian patriotic liturgy. The article seeks to analyse the different instances of collective memory associated with the celebration.